Transformasi Metode Pembelajaran Pendidikan Agama Kristen Di Era Digital - Martin Putra Hura; Septiniar Laoli; Marisa Aulia Gea (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Education has experienced rapid development along with the growing technological advances. This can happen because of the learning methods and systems supported by digital technology. This development shows the strong influence of the digital era. In the learning process, especially Christian Religious Education, one must have the ability to choose the right approach and method according to the material and learning objectives. The method used in this research is a qualitative literature/descriptive study. The purpose of this research is to explore various methods and digital technologies that can be used in Christianity learning, as well as evaluating their impact on students' understanding, learning motivation, and active participation in Christianity materials. The results of this discussion explain the learning methods that Christian Religious Education can use in this increasingly sophisticated digital era. The implication is that there is better accessibility in learning. To achieve these implications, it is necessary to transform learning methods to help each student understand and face moral dilemmas that arise in the use of technology in line with Christian teachings on ethics and morality.